Macro Economic Challenges and Third Party Funds of Islamic Commercial Banks in Indonesia - Anik, Anik; Prastiwi, Iin Emy (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2018)
This article aims to determine the effect of inflation, the BI Rate, the exchange rate of the rupiah to the US dollar, and the amount of money supply for Third Party Funds (TPF) in Indonesians’ Islamic Banks during 2013-2016. This research method uses multiple regression analysis with time series data; gathering data from 48 samples of which are monthly data on the variables. The result of this research find that the inflation and exchange rate variables have no significant effect on TPF, while the BI Rate variable and the money supply have a significant effect on TPF. In doing so, Islamic banking can pay serious attention to the BI rate and the money supply and in this study the BI rate on the direction of TPF. Keywords: inflation, BI rate, exchange rate, Third Party Funds